PERANAN JAKSA PENUNTUT UMUM DALAM PENYELESAIAN PERKARA MONEY LAUNDERING PADA KASUS NOMOR 646/PIDANA/B/2013/PENGADILAN NEGERI PEKANBARU - Ariati, Nova; Effendi, Erdianto; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Based on watchfulness result and discussion, money loundering in case Nomor 646/Pidana/B/2013/Pengadilan Negeri Pekanbaru, from facts revealed at conference have been known that any element in third accusation more subsidair fulfilled, break section 3 law Nomor 8 year 2010, paragraph 372 KUHP and paragraph 378 KUHP. In case apply elements decision Nomor 646/Pidana/B/2013/Pengadilan Negeri Pekanbaru, judge of district court Pekanbaru appropriate apply elements in third accusation more subsidair from public prosecutor, the elements:a. Everyoneb. Get or dominate location, transfer, payment, gift, contribution, entrusted, exchange or use wealth treasure detect it or fitting detectt it be doing an injustice result.c. As one who does, order to do or join in to dod. Several deeds connecteds, so that thereby must be looked at as one deed sustaiined.Base judge deliberation in drop criminal in case Nomor 646/Pidana/B/2013/Pengadilan Negeri Pekanbaru, in drop criminal decision,considering base fallen down thecriminal, that is with base in valid proof tools, proved at conference that cover witnesses explanation, proof goods, and explanation defendants delf.Towards valid proof tools that subbimeted in conference, and reviewed from conformity between proof tools one by means of ohter proof, with consodering verification value each proof. All juridical fact rvealed at conference appropriate and proved the true fulfil elements in third accusation more subsidair.Keywords : Role-Prosecutor – Money Loundering